Development of a human herpesvirus 8-negative effusion-based lymphoma during treatment with dasatinib for chronic myeloid leukemia - Suyama, Takahiro; Hagihara, Masao; Matsui, Naruaki; Irie, Rie; Osamura, Yoshiyuki; Sakai, Tetsuo; Watanabe, Shouichi; Umemoto, Shintarou; Miyao, Naoki (Journal of Clinical and Experimental Hematopathology, 2023)
We present the case of an 85-year-old male patient diagnosed with human herpesvirus 8 (HHV8)-negative effusion-based lymphoma (EBL) that developed from long-lasting pleural effusion (PE) induced by dasatinib treatment for chronic myeloid leukemia (CML). After the onset of this disorder, dasatinib treatment was discontinued and drainage was performed to regress the effusion. The major molecular response (MMR) was thus lost. The patient did not tolerate nilotinib treatment, but bosutinib was successful in restoring MMR. During these clinical courses, the patient suffered from a recurrence of EBL, which was treated with rituximab-based chemotherapy. The PE sample just before the 3rd cycle of chemotherapy revealed the proliferation of CD57-positive T cells, along with the disappearance of lymphoma cells. Anti-tumor immunity may have been activated following the immunochemotherapy in the undisturbed immunological environment when both EBL and CML almost regressed. After four cycles of R-CVP therapy, the patient has been in remission for 16 months and no longer requires drainage.